Judicial Agenda Setting Through Signaling and Strategic Litigant Responses - Vanessa Baird; Tonja Jacobi (Washington University Journal of Law & Policy, 2009)
The purpose of this Essay is to present the theory and empirical evidence that strategic interaction between litigants and Justices transforms the U.S. Supreme Court’s agenda. More specifically, it proposes that Supreme Court Justices shape the Court’s agenda by providing signals to litigants about the sort of cases they would like to see, and litigants consider those signals when deciding whether or not to pursue a given case.
Keywords: Judicial process; Judicialization of politics; Empirical analysis; Judicial signaling